Decision Tree Algorithm Based Portable Automation Device to Reduce Electricity Usage on Television - Nia Maharani Raharja; Ipin Prasojo (Journal of Telecommunication Control and Intelligent System, 2021)
Abstract— Almost all television sets are equipped with a timer, but sometimes we ignore it. Due to falling asleep or suddenly being left behind, we forget to turn off the television which eventually turns on the television without anyone watching. In such a case, of course there is a waste of electricity. This article contributes to designing devices that can turn off the television when no one is watching without setting the timer that comes with the television first and portable devices for all television brands. The tool is designed using an AVR microcontroller with type AT90USB162. The PIR sensor is used to detect people in front of the television. The sensor data is processed using an AVR type microcontroller and connected to a relay to turn the television on and off. The device is designed to detect the movement of people in front of the television, so that the television turns on when people watch it.